NFAT-Induced Histone Acetylation Relay Switch Promotes c-Myc-Dependent Growth in Pancreatic Cancer Cells - König, Alexander (2009)
BACKGROUND & AIMS: Induction of immediate early transcription factors (ITF) represents the first transcriptional program controlling mitogen stimulated cell cycle progression in cancer. Here, we examined the transcriptional mechanisms regulating the ITF protein c-Myc and its role in pancreatic cancer growth in vitro and in vivo. METHODS: Expression of ITF proteins were examined by RT-PCR and immunoblotting, and their implications in cell cycle progression and growth were determined by flow cytometry and [(3)H] thymidine incorporation. Intracellular Ca(2+) concentrations, calcineurin activity and cellular NFAT distribution were analyzed. Transcription factor complex formations and promoter regulation were examined by immunoprecipitations, reporter gene assays and chromatin immunoprecipitation (ChIP). Using a combination of RNAi knockdown technology and xenograft models we analyzed the significance for pancreatic cancer tumor growth. RESULTS: Serum promotes pancreatic cancer growth through induction of the proproliferative NFAT-c-Myc axis. Mechanistically, serum increases intracellular Ca(2+) concentrations and activates the calcineurin/NFAT pathway to induce c-Myc transcription. NFAT binds to a serum responsive element within the proximal promoter, initiates p300-dependent histone acetylation and creates a local chromatin structure permissive for the inducible recruitment of ELK-1, a protein required for maximal activation of the c-Myc promoter. The functional significance of this novel pathway was emphasized by impaired c-Myc expression, G1-arrest and reduced tumor growth upon NFAT depletion in vitro and in vivo. CONCLUSION: Our study uncovers a novel mechanism regulating cell growth and identifies the NFAT-ELK complex as modulators of early stages of mitogen stimulated proliferation in pancreatic cancer cells.